VARIASI POLA SIDIK JARI SOROH BRAHMANA SIWA DI BALI - Bajing Agastya, Ida Bagus; Junitha, I Ketut; Wirasiti, Ni Nyoman (SIMBIOSIS, 2017)
ABSTACT Research was conducted to determine the patterns of Brahmana Shiva fingerprint in Bali. The fingerprint samples as many as 240 people, which consist of 120 men and 120 women from four generation of Brahmana Shiva in Bali. The fingerprints were collected using a fingerprint pad then the data were analyzed using Chi–Square test, Student-t test, Dankmerijer index and Furuhata index. The result of fingerprints examination shown that there were four fingerprints pattern i.e. arch (A), loop ulnar (LU), loop radial (LR), and whorl (W) from four sub clan (Brahmana Manuaba, Kemenuh, Keniten, Mas), with different frequencies and anequal distribution from each fingers and both hands. The arch (A) pattern in clan Brahmana Manuaba and Kemenuh have the same 0.83 % frequencies, while the frequencies of Keniten 1.17 % and Mas 1.67 %. The frequencies of Loop ulnar (LU) pattern from clan Brahmana Mas were 42.66 %, Manuaba 36 %, Keniten 39 %, and Kemenuh 34.33 %. The frequency of loop radial (LR) pattern from clan Brahmana Manuaba were 42.17 %, Keniten 41.83 %, Mas 37.83 %, and Kemenuh 29.51 %. The frequencies of whorl (W) pattern from sub clan Brahmana Kemenuh, Manuaba, Keniten, and Mas were 35.33 %, 22 %, 18 %, and 17.83 %, respectively. The result show a significant differences between sub clan Mas and Kemenuh using Dankmerijer Index (DI). The result show a significant differences between sub clan Kemenuh with Mas, Keniten and Manuaba using Furuhata Index (FI). Total Ridge Count between men and women of Brahmana Shiva offspring showed unsignificantly diferences at level 5%. However, there was a significant difference of Total Ridge Count from sub clan Manuaba with Mas, Kemenuh, and Keniten. Keywords : fingerprints, arch, loop, whorl, clan brahmana shiva.